Analisis Kinerja Keuangan Dengan Menggunakan Rasio Keuangan Pada Perusahaan Semen Yang Terdaftar Dalam Bursa Efek Jakarta (Tahun 2005 – 2006) - Rini Widianingsih; Sudrajat Sudrajat (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2011)
ABSTRACT Financial performance is one of the principal dimensions of the firm, because financial performance reflected the company's ability to manage and allocate its resources. Many different interests on the financial performance report, depending on the viewpoint taken. The management perspective interested in the success of the company in order to carry out basic tasks and functions, the owners concerned about the success of the company for the loan principal and interest may continue to be paid in installments. This study uses financial ratio analysis method to assess the effectiveness of the company, and trend analysis to determine financial performance. Ratio and trend equations obtained compared to industry ratios. Ratios restricted on management perspective are the ratio of profit margin, asset turnover ratio and return on equity, return on equity and the results are represented by corporate profits. Whereas from the viewpoint of lenders used ratio is the ratio of liquidity and financial levers which consists of forests to assets ratio, the ratio of long-term debt to equity and debt to equity ratio. Keyword: performance, financial ratios